LEGAL REGULATION OF GENDER EQUALITY IN UKRAINE - Tsytsiura, Volodymyr; Medvid, Liudmyla; Ryndych, Daria (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2023)
The purpose of this paper is to research different approaches towards determination of the concepts of “legal regulation”, “legislation” and the structure of the legislation system, analysis of legislation system of Ukraine in the domain of gender equality in Ukraine. Using general philosophical and scientific methods of cognition as the methodological basis for the study, the article provides a thorough analysis of various scientific and doctrinal approaches in the determination of the terms "legal regulation" and "legislation" as well as shaping the structure of the legislative system in the field of gender equality. One of the most significant methods that were implemented to highlight and establish the qualitative aspects of the phenomenon under the study is the dialectic method of cognition. Using to the historical method, viewpoints regarding the essence, content, and objectives of the legal system’s structure regarding to the gender equality have been researched and refined. The results of the research contain the development of theoretical provisions to determine the concept of legislation as a collection of Ukrainian laws, resolutions of the Verkhovna Rada, Decrees of the President of Ukraine, and Resolutions of the Cabinet of Ministers of Ukraine that are adopted in accordance with Constitution and Ukrainian laws, as well as subordinate legal acts of ministries and other executive bodies that have received state registration. These approaches contribute to the definition of the legislation as a hierarchical unified system of legal acts with distinct legal authority. Understanding the concepts of "legal regulation" and "legislation" provided a basis for the establishment of the legal system in the sphere of gender equality. It was additionally discovered that although gender equality laws and procedures in Ukraine are not optimal, they do provide an avenue for the process of guaranteeing gender equality. Discussion: this research revealed that the definition of "legislation" has no place in the Ukrainian laws. However, the term "legislation" is frequently used in multiple types of legal acts without any clarification, therefore requiring the establishment of the term at the legislative level. Additionally, the structure of the legal system in the context of gender was examined in this paper. Furthermore, it concluded that the gender equality laws as they currently exist must be improved, that becomes possible by taking into consideration the most recent advancements in domestic science and international legal regulations in the relevant field.